Family Education of Tengger People In Instilling Islamic Education Values towards Children - Reni Anjasari; Ahmad Marzuki; Munif Shaleh (Universitas Yudharta Pasuruan, 2020)
Family education is very important if the existing pattern of society is a pluralistic society like in Tengger. The purpose of this study are to: 1) Describe the understanding of Tengger ethnic parents about Islamic education and 2) Analyze the role of parents in instilling the values ​​of Islamic education toward childrens. The author chose a qualitative approach and data collection techniques are three techniques: interviews, observation and documentation. The results of this study include: 1) Understanding of parents about the values ​​of Islamic education is classified by: a) Aqeedah in the form of belief where as Muslims have different beliefs that are different from friends of non-Muslim children , b) Shari'a in the form of commands and prohibitions as well as permissible in the law ranging from worship to mu'amalah and c) Morals that foster awareness to do good by preserving morals and doing it sincerely and 2) The role of parents in instilling Islamic educational values, namely acting as educators and protectors for their children. Then various ways or methods are: a) Modeling, b) the habit method, c) the method of advice and d) the method of supervision.